Beyond borders: Exploring the mental, emotional, and spiritual significance of Hajj - Abdulaziz H. Alzeer; Jude Abuzinadah (Annals of Thoracic Medicine, 2024)
For Muslims all across the world, the desire to participate in the religious rites of the Hajj (pilgrimage to Mecca) which stands as one of the five pillars of Islam is a heartfelt longing. It stands for the pinnacle of devotion and spiritual gratification, luring followers to the most sacred city in Islam for a life-changing journey of faith, comradery, and submission to Allah. Muslims hold Mecca in the highest regard; it is a source of endless inspiration and devotion throughout their lives, as seen by their desire to undertake the Hajj and Umrah. The pilgrimage encompasses a series of synchronized rituals and acts of worship, each holding its unique spiritual meaning, and serve as a powerful testament to the universal nature of Islamic teachings. These rituals have a significant impact on Muslims’ mental and spiritual well-being. Hajj elicits a spectrum of feelings; creates unity, humility, and thankfulness; and encourages self-reflection as well as personal development. It also instills a sense of spiritual fulfillment. Hajj transcends personal boundaries, strengthening a pilgrim’s sense of connection to the larger Muslim community that rejuvenates their hearts and souls toward the teaching of Islam. Hence, it is imperative to explore in depth this transformative journey, illuminating the mental, emotional, and spiritual dimensions that bind Muslims across the globe.